APLIKASI PERANGKAT LUNAK SISTEM AKUISISI KECEPATAN REACTION WHEEL (SOFTWARE APPLICATION OF REACTION WHEEL SPEED ACQUISITION SYSTEM) - Harry Septanto (Jurnal Teknologi Dirgantara, 2017)
Transfer of technology activity through reverse engineering is an effort done by developing country in order to decrease technology gap, including in satellite technology, from developed country. To perform measurement anddata acquisition in order to extract design information of a satellite component are the first step in reverse engineering process. This paper reports the result of research on the development of data acquisition software for satellite actuator called reaction wheel speed. In satellite development phase, the wheel speed acquisition system is also possible to be utilized as a testing tool for componente level verification. The wheel speed data obtained from the experiment was represented in graphic of transient response. Based on the data analysis, the developed data acquisition system was possible to be utilized to measure dynamic characteristic of the reaction wheel unit in order to extract its design information. Meanwhile, the analysis done has represented basic part of component level verification test. This fact showed that the developed acquisition system was also possible to be used as testing tool in satellite development phase.  ABSTRAKKegiatan alih teknologi melalui reverse engineering merupakan upaya yang dilakukan oleh negara berkembang dalam rangka memperkecil jarak ketimpangan dari negara maju dalam hal teknologi, termasuk teknologi satelit. Melakukan pengukuran dan akuisisi data dalam rangka mengurai informasi desain suatu komponen satelit adalah tahap pertama proses reverse engineering. Makalah ini melaporkan hasil penelitian mengenai pengembangan perangkat lunak sistem akuisisi data kecepatan wheel dari sebuah aktuator satelit yang disebut reaction wheel unit. Dalam aspek fase pengembangan satelit, sistem akuisisi data ini dapat digunakan sebagai perangkat pengujian untuk verifikasi di tingkat komponen. Data kecepatan wheel, yang diperoleh dari eksperimen yang dilakukan, ditampilkan dengan grafik respon transien. Berdasarkan analisis atas data tersebut, sistem akusisi data yang dikembangkan menjanjikan untuk digunakan dalam rangka pengukuran karakteristik dinamik reaction wheel sebagai upaya mengurai informasi desainnya. Selain itu, analisis yang telah dilakukan merepresentasikan bagian dasar dari tahap verifikasi di tingkat komponen. Hal ini menunjukkan bahwa sistem akusisi data ini menjanjikan untuk digunakan sebagai perangkat pengujian di dalam fase pengembangan satelit.